Exploring the feasibility of integrating health, nutrition and stimulation interventions for children under three years in Nepal's health system: A qualitative study. - Sophiya Dulal; Naomi M Saville; Dafna Merom; Kalpana Giri; Audrey Prost (Public Library of Science (PLoS), 2023)
Community-based primary care settings are a potential entry point for delivering Early Childhood Development (ECD) interventions in Nepal. Past studies have suggested that integrating stimulation with nutrition interventions is an effective way to deliver multiple benefits for children, but there is limited knowledge of how to do this in Nepal. We conducted a qualitative study in Nepal's Dhanusha district to explore how stimulation interventions for early learning could be integrated into existing health and nutrition programmes within the public health system. Between March and April 2021, we completed semi-structured interviews with caregivers (n = 18), health service providers (n = 4), district (n = 1) and national stakeholders (n = 4), as well as policymakers (n = 3). We also carried out focus group discussions with Female Community Health Volunteers (FCHVs) (n = 2) and health facility operation and management committee members (n = 2). We analysed data using the framework method. Respondents were positive about introducing stimulation interventions into maternal and child health and nutrition services. They thought that using health system structures would help in the implementation of integrated interventions. Respondents also highlighted that local governments play a lead role in decision-making but must be supported by provincial and national governments and external agencies. Key factors impeding the integration of stimulation into national programmes included a lack of intersectoral collaboration, poor health worker competency, increased workload for FCHVs, financial constraints, a lack of prioritisation of ECD and inadequate capacity in local governments. Key barriers influencing the uptake of intervention by community members included lack of knowledge about stimulation, caregivers' limited time, lack of paternal engagement, poverty, religious or caste discrimination, and social restrictions for newlywed women and young mothers. There is an urgent need for an effective coordination mechanism between ministries and within all three tiers of government to support the integration and implementation of scalable ECD interventions in rural Nepal.